If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 4(5x + -4) = 7 + -3(2x + 1) Reorder the terms: 5 + 4(-4 + 5x) = 7 + -3(2x + 1) 5 + (-4 * 4 + 5x * 4) = 7 + -3(2x + 1) 5 + (-16 + 20x) = 7 + -3(2x + 1) Combine like terms: 5 + -16 = -11 -11 + 20x = 7 + -3(2x + 1) Reorder the terms: -11 + 20x = 7 + -3(1 + 2x) -11 + 20x = 7 + (1 * -3 + 2x * -3) -11 + 20x = 7 + (-3 + -6x) Combine like terms: 7 + -3 = 4 -11 + 20x = 4 + -6x Solving -11 + 20x = 4 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -11 + 20x + 6x = 4 + -6x + 6x Combine like terms: 20x + 6x = 26x -11 + 26x = 4 + -6x + 6x Combine like terms: -6x + 6x = 0 -11 + 26x = 4 + 0 -11 + 26x = 4 Add '11' to each side of the equation. -11 + 11 + 26x = 4 + 11 Combine like terms: -11 + 11 = 0 0 + 26x = 4 + 11 26x = 4 + 11 Combine like terms: 4 + 11 = 15 26x = 15 Divide each side by '26'. x = 0.5769230769 Simplifying x = 0.5769230769
| 5/6x-2/11x | | -a^2+11a=0 | | 5/6X+6/7-2/11X | | 2x+10+4(-x)=(-x)+(-20) | | 10d+5=7d+32 | | 2/5x+3=9 | | (1.49+0.59+0.49)=30.84+0.30 | | (7x-8)(3x+9)= | | fx=-1x+x^3 | | 4/5=c/7 | | 3-x-9+15x= | | 3x+(-2x)+x=3x+18 | | 3t+8=5t+8-2t | | 3(x-4)=-1.2 | | 100x-29=42671 | | 1/4x-1/8x=3-1/16x | | 60x=100 | | 7(a+2)=34.3 | | x*3=18 | | 0.25y-3.5=0.15y+1-0.8y | | 100x-29=100(426.71) | | -2/3x+2=6 | | 3(-2x+1)-4(-x)=-x+19 | | 3(-2x+1)-4(-x)=x+19 | | 3t+2(t+1)+7t+6=-16 | | 3x+6=3x-12 | | 7m-25=-32+6m | | z-42=-41 | | 20=5c-3 | | 2(x-3)=3x+3 | | x-0.6=9.36 | | 7e-9=19.7 |